1999
DOI: 10.1007/s002329900540
|View full text |Cite
|
Sign up to set email alerts
|

Mouse VDAC Isoforms Expressed in Yeast: Channel Properties and Their Roles in Mitochondrial Outer Membrane Permeability

Abstract: The channel-forming protein called VDAC forms the major pathway in the mitochondrial outer membrane and controls metabolite flux across that membrane. The different VDAC isoforms of a species may play different roles in the regulation of mitochondrial functions. The mouse has three VDAC isoforms (VDAC1, VDAC2 and VDAC3). These proteins and different versions of VDAC3 were expressed in yeast cells (S. cerevisiae) missing the major yeast VDAC gene and studied using different approaches. When reconstituted into l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
116
0
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(130 citation statements)
references
References 32 publications
9
116
0
5
Order By: Relevance
“…We found little NADH oxidation in mitochondria expressing VDAC3, suggesting minimal intrinsic membrane permeability ( Supplementary Fig. 17); this is consistent with previous reports that VDAC3 does not gate well in vitro 20 . Finally, we found that an inactive analogue of erastin (erastin A8, Fig.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…We found little NADH oxidation in mitochondria expressing VDAC3, suggesting minimal intrinsic membrane permeability ( Supplementary Fig. 17); this is consistent with previous reports that VDAC3 does not gate well in vitro 20 . Finally, we found that an inactive analogue of erastin (erastin A8, Fig.…”
supporting
confidence: 92%
“…20 ). As a control for mitochondrial intactness, parallel assays were run using hypotonically shocked mitochondria.…”
Section: Nadh Oxidation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…9 However, these different effects are not supported by the apparent redundancy in the electrophysiological properties of the isoforms. 19,20 Mitochondrial [Ca 2 þ ] is commonly regarded as an important determinant in cell sensitivity to apoptotic stimuli. 21 Indeed, mitochondrial Ca 2 þ accumulation acts as a 'priming signal' sensitizing the organelle and promoting the release of caspase cofactors, both in isolated mitochondria as well as in intact cells.…”
mentioning
confidence: 99%
“…Channels formed by mouse VDAC-2 are noisier than VDAC-1 (4,23), suggesting alternate functions for the less abundant hVDAC-2 and hVDAC-3 isoforms other than the "ion conductance" usually associated with these proteins. The abundance of cysteine residues in hVDAC-2 is particularly intriguing (supplemental Fig.…”
mentioning
confidence: 99%